A Production and operations management study on Jacinto Iron and Steel Sheets Corporation (JISSCOR) - Estrada, Eric; Galon, Jude; Lim, Fritz; Ogardo, Ethel (College of Engineering, 2000)
This study dealt with the applications of the tools and techniques of Production and Operations Management to the production system of the Jacinto Iron and Steel Sheets Corporation (JISSCOR), a company engaged in the manufacture of GI sheets and other iron and steel products. This focused on the company's newest product -- the Steel Deck. Using the Streamline diagnostic Chart in problem analysis, the root problems of the company were identified. These problems are the under-utilization of resources, unreliable forecast techniques, absence of supplier evaluation procedures, and poor inventory policy. These problems are further analyzed and detailed recommendations were presented. Addressing the problem of unreliable forecasting technique, the demand during the most recent year is evaluated to recommend the forecasting technique most applicable -- the Exponential Smoothing Technique. Other recommendations include the use of the Analytical Hierarchy Process in supplier selection, the 2 -- shift per production day increasing the utilization of their resources like workers and the computation of the Economic Lot Size to improve the present inventory policy.